Positive Politeness Strategies in the Main Character “Moana II” Movie Utterances - Amanda Dwi Juliatiningrum (Penerbit STKIP PGRI Bangkalan, 2025)
This study analysis discusses how often positive politeness appears in the main character's dialogue in the film